Integrating refugees in the Rhine-Neckar-Region: Initial evidence from an inclusive soccer project - Gerard van den Berg; Michael Kolb; Martin Lange; Friedhelm Pfeiffer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
The study analyses data from a survey conducted in July 2016 in the German Rhine-Neckar region among a group of male refugees who participate in a small inclusive soccer project or are part of a control group. Our main findings with respect to labour market integration and the effect of program participation can be summarized as follows. The total group of 81 responding male asylum seekers is on average 23 years old, has on average spent nearly nine years in education and already accumulated five years of work experience in their home countries or on their way to Germany. They report on average a good health and are fairly optimistic about finding work in Germany. However, although they are on average already nine months in Germany only 36 percent were searching for a job, while 14 percent report that they were working at the time of the survey. Thus, it seems that the responding refugees are equipped with a good health, reasonable work experience and motivation, and a low level of education, comparted to Germans of the same age group. 28 survey participants engaged in the soccer project. Most of them indicated that they would like to participate more frequently. Responding refugees, who participate in the soccer project report that they visit German natives in their homes more often than the control groups, which hints at some initial positive short run integration effects. According to our experience respondents enjoyed collaboration in the survey. Since the number of respondents is small our findings are preliminary in nature. Future research that intends to more deeply assess causal impacts needs to rest on significantly larger samples and panel data.
Additional information: This research has been conducted as part of "Real World Laboratory: Asylum Seekers" - A joint research project of Heidelberg University of Education and ZEW Mannheim.
Keywords: 330; Social integration; refugees; men; soccer; Rhine-Neckar region; Soziale Integration; Flüchtlinge; Männer; Fußball; Rhein-Neckar-Gebiet